Case study of a private condominium project on its contractual related issues - Fong, Sun Yong. (2008)
With the increasing knowledge and the awareness of their contractual rights, parties involved in construction, namely employers, consultants, main contractors and subcontractors had shaped a rising trend of hauling each other to court or arbitration. The financial crisis in the region in 1997/98 had made the situation worst.